Mixed matrix membranes containing aspartic acid functionalized graphene oxide for enhanced oil-water emulsion separation - Omnya Abdalla (17100211) (2020)
Polysulfone (PS) mixed matrix membranes (MMMs) containing aspartic acid (AA) functionalized graphene oxide (fGO) with improved flux, oil rejection, and resistance to fouling were fabricated via phase inversion. The membranes hydrophilicity, morphology, porosity, and mechanical properties were analyzed and the impact of fGO loading on them was investigated using contact angle measurements, SEM, AFM, and dynamic mechanical analysis. The results revealed an increase in the membrane’s hydrophilicity, water permeability and oil rejection at very low fGO loadings, i.e., 0.05 – 0.2 wt.%, but no further enhancement was obtained at higher loadings, i.e., 0.4−0.8 wt.%. Water permeability increased by 97 % at 0.2 wt.% fGO membrane compared to pristine membrane and oil rejection reached 97.9 % upon filtration of 200 mL oil emulsion. Moreover, the MMM containing 0.2 wt.% fGO exhibited enhanced fouling resistances as demonstrated by slow flux decline and 90 % flux recovery after two cycles of fouling with bovine serum albumin (BSA).The results indicated that the carboxylic and amino groups introduced by AA functionalization were responsible for the enhanced hydrophilicity and fouling resistance. PS/fGO MMMs provided significant enhancement in performance, mechanical properties and fouling resistance at very low fGO concentration that does not affect the rheology of PS-fGO formulation and therefore requires no alteration to the commercial phase inversion process. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2020.104269